Solo mio! : un cuento del bebe de la mochila = Mine! : a backpack baby story - Cohen, Miriam, 1926-; Cohen, Miriam; Cohen, Miriam (New York, NY : Star Bright Books, 2005)
Backpack baby learns to share with his daddy.
Cover title.
Board book.
Text in English and Spanish.
Keywords: Sharing -- Juvenile fiction; Father and child -- Juvenile fiction; Participacion y reparticion -- Novela juvenil; Padre e hijos -- Novela juvenil